A Preliminary Study of Pilgrimage Tourism in Barahachhetra, Nepal - Kunwar, Ramesh Raj; Thapaliya, Nabin (The Gaze: Journal of Tourism and Hospitality, 2021)
Pilgrimage is an age-old phenomenon for people of all religions. Pilgrimage is often been defined as a journey resulting from religious causes, externally to a holy site, and internally for spiritual purposes and internal understanding. For the Hindus, Pilgrimage is associated with Moksha (liberation), one of the four Purusharthas (virtues), the other three being Artha (material value) Dharma (righteousness), and Kama (pleasure). The concept of pilgrimage tourism in the Hindu tradition is a recent one. In Nepal, where tourism has largely remained a seasonal business, pilgrimage tourism can be a perennial source of income especially because Nepal is home to some of the world’s most important sacred Hindu and Buddhist pilgrimage destinations. It is also noteworthy that according to 2011 official census in Nepal, more than 80 percent of the residents follow Hinduism (Central Bureau of Statistics, 2012, p.4) and Nepal shares a free border with India, the country with the largest number of Hindu residents, in absolute terms, in the entire world. Barahachhetra in Nepal is as important as other pilgrimage destinations in Nepal, however, no studies have been carried out so far on the status and potential of pilgrimage tourism in Barahachhetra. The authenticity of the pilgrimage sites, the hospitality culture and the peace experienced by pilgrims together provide a memorable pilgrimage tourism experience for the pilgrimage tourists visiting Barahachhetra. The prospect of pilgrimage tourism in Barahachhetra is immense and has a direct bearing on the preservation of the religious and cultural heritages as well as the economic condition of the residents therein. A coordinated approach initiated at the highest level of governance is required to study, promote and sustain pilgrimage tourism in Barahachhetra. In this study both pilgrimage tourism and religious tourism interchangeably used. Though spiritual tourism has become recently evolved, the authors did not visit on it although efforts have been made to highlight its significant in the introduction.